Audit committee effectiveness, internal audit function, firm-specific attributes and internet financial reporting: a managerial perception-based evidence - Bananuka, Juma; Korutaro Nkundabanyanga, Stephen (Journal of Financial Reporting and Accounting, 2022)
This study aims to examine the contribution of audit committee effectiveness (ACE), internal audit function (IAF) and firm-specific attributes to internet financial reporting (IFR). It also seeks to understand which ACE and IAF attributes contribute to variances in IFR. Design/methodology/approach – Data are collected through a questionnaire survey of 40 financial services firms. Findings – The analysis shows that ACE and IAF significantly contribute to positive variances in IFR. It also shows that among the firm-specific attributes, only capital structure significantly contributes to positive variances in IFR. Audit committee meetings and authority contribute significantly to positive variances in IFR unlike audit committee expertise and independence. In terms of the IAF attributes, the risk management role and the regulatory compliance role contribute significantly to positive variances in IFR as compared to the governance processes role and evaluation of the internal control role. Originality/value – This study enhances our understanding of the relationship between ACE, IAF, firmspecific attributes and IFR in an environment where IFR is not mandated and where corporate governance practices are very much in infancy. This is especially so given that for the first time, to the best of the authors’ knowledge, the contribution made by ACE, IAF and firm-specific attributes in IFR using evidence from an African developing country (Uganda) is now documented in a single study.
Keywords: Internet financial reporting; Audit committee effectiveness; Internal audit function; Diffusion of innovation theory; Firm-specific attributes